[Freshman girls, dressed in white and wearing garlands, performing 'Flower Dance' at the annual Athletic Carnival] - Frank Aston::::::photographer::: (1915)
Feb. 26, 1915. Freshman girls, dressed in white and wearing garlands, performing 'Flower Dance' at the annual Athletic Carnival. See Polytechnic J. 1915 for another image of same subject.